2020
DOI: 10.1016/j.tranon.2019.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Whole Fruit Phytochemicals Combating Skin Damage and Carcinogenesis

Abstract: Skin is arguably the largest organ of the body and is continuously subjected to intrinsic, extrinsic, and environmental stresses. Therefore, skin developed elaborate mechanisms to maintain homeostasis, including antioxidant, antiinflammatory, and DNA damage repair capabilities. However, repeated and excessive stresses can overwhelm these systems, causing serious cutaneous damages, including skin carcinogenesis. Phytonutrients present in the diet possess a myriad of health-promoting effects by protecting skin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…They are known to be useful against diseases linked to free radicals, DNA damage and carcinogenesis as well as in the prevention of oxidative reactions in foods. They are also believed to possess anti-inflammatory and antimicrobial properties ( Zhang et al, 2015 ; Lee et al, 2017 ; Mintie et al, 2020 ). Several plants and plant parts hold promise as rich reservoirs of antimicrobial compounds and thus, require sustained pharmacological investigations.…”
Section: Resultsmentioning
confidence: 99%
“…They are known to be useful against diseases linked to free radicals, DNA damage and carcinogenesis as well as in the prevention of oxidative reactions in foods. They are also believed to possess anti-inflammatory and antimicrobial properties ( Zhang et al, 2015 ; Lee et al, 2017 ; Mintie et al, 2020 ). Several plants and plant parts hold promise as rich reservoirs of antimicrobial compounds and thus, require sustained pharmacological investigations.…”
Section: Resultsmentioning
confidence: 99%
“…PCa incidence increases with age, which makes it more difficult to manage this disease. Recent studies demonstrating the beneficial effect of modifying dietary habits have been suggested to manage multiple diseases, including PCa [ 3 , 62 , 63 ]. Here, we found that dietary supplementation with the grape antioxidants quercetin and resveratrol together had significant antitumor effects against PCa in both prevention and intervention settings.…”
Section: Discussionmentioning
confidence: 99%
“…For physical activity ascertainment, the Iranian Short Version of International Physical Activity Questionnaire (IPAQ) was given to the participants (Hu, 2002; Moghaddam et al., 2012). Physical activity levels of each participant were categorized as active and inactive based on the guideline of the short form of IPAQ (Mintie et al., 2020).…”
Section: Methodsmentioning
confidence: 99%